THE READABILITY OF READING TEXTS IN ENGLISH TEXTBOOK FOR GRADE VIII STUDENTS OF SMP NEGERI 1 KABANJAHE 2016/2017 - Rinaldi Masda Syahputra and Johan Sinulingga (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2017)
This research analyzed the readability of reading texts taken from English textbooks for grade VIII students of SMP Negeri 1 Kabanjahe of 2016/2017 entitled English in Focus published by Pusat Perbukuan Departemen Pendidikan Nasional. Being important a textbook as the most used in sources of a class, textbook should be readable and appropriate for the students especially for the reading texts inside it. The goal of this research was to find out how is the readability of those reading texts in the textbook.To describe and investigate the readability, this research used a readability formula measurement called SMOG Grading Formula which is found by G. Harry Mc. Laughlin. The source of the data were 20 reading texts taken randomly from English in Focus textbook.The major findings of the study showed that the readability of 20 reading texts were in the variety level for students within 5th elementary school to the 10th grade high school students level, and it found that 13 of 20 reading texts or about 65% of the data are appropriate for the 8th grade students who are the user of the book. Meanwhile, this research also found reading texts which are not appropriate for the students. There are 3 reading texts are too easy and 4 are too difficult for them. So, 35% reading texts in the data is not appropriate for 8th grade students.